ANTICIPATION GUIDE : A STRATEGY OF TEACHING READING COMPREHENSION - Andri Defrioka (Universitas Negeri Padang, 2013)
This paper reveals an alternative model for teaching reading comprehension at senior high schools. An anticipation guide is a comprehension strategy that is used before reading to activate students' prior knowledge and build curiosity about a new topic. Before reading, students listen to or read several statements about key concepts presented in the text; they're often structured as a series of statements with which the students can choose to agree or disagree. Anticipation guides stimulate students' interest in a topic and set a purpose for reading. They also create curiosity for the reader, provides the reader with a purpose, gives a focus to the reading and can be a way for the teacher to be cued into how much scaffolding his/her students need. The teacher generates a number of statements based on the reading. Some of the statements are confirmed by the reading, while other statements are contradicted by the reading. Students are asked to evaluate the accuracy of the statements. Students from differing opinions can explain their thinking. This model is designed and hopefully will be useful for English teachers who are training students to read and face the implementation of Curriculum 2013 at senior high schools.